Forecasting Residential Electrical Consumption For The City Of Salta, Argentins - Zanek, Franco (2019)
This work presents a model that forecasts the residential electricity demand of the City of Salta. The consumption habits of the residents of the dwellings helped the development of the proposed model, which include the turning on and off of the artifacts, aspects related to the presence or not of peo-ple in the homes, including the day-night simulation, of temperature environ-ment and relative humidity. Surveys and interviews were conducted to characte-rize the electricity consumption routines in the city's housing. The techniques proposed in the theory of probability and statistics helped the development of the functions that are integrated to form the proposed model